Psychological Preparation of Athletes - Nazarova, N. E.; Ibragimova, A. A. (Journal of Innovation in Education and Social Research, 2024)
It is important for athletes to psychologically and mentally prepare themselves during pre-competition training. In this case, it is appropriate for the coaches to give proper instructions to the trainee based on their skills and qualifications.